Use of sugarcane industrial by-products for improving sugarcane productivity and soil health - M. L. Dotaniya; S. C. Datta; D. R. Biswas; C. K. Dotaniya; B. L. Meena; S. Rajendiran; K. L. Regar; Manju Lata (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Sugarcane industries are age-old industrial practices in India which contribute a significant amount of byproducts as waste. Handling and management of these byproducts are huge task, because those require lot of space for storage. However, it provides opportunity to utilize these by-products in agricultural crop production as organic nutrient source. Therefore, it is attempted to review the potential of sugar industries by-products, their availability, and use in agricultural production. Methods A large number of research experiments and literatures have been surveyed and critically analyzed for the effect of sugarcane by-products on crop productivity and soil properties. Results Application of sugar industries by-products, such as press mud and bagasse, to soil improves the soil chemical, physical, and biological properties and enhanced the crop quality and yield. A huge possibility of sugarcane industries by-products can be used in agriculture to cut down the chemical fertilizer requirement. If all the press mud is recycled through agriculture about 32,464, 28,077, 14,038, 3434, 393, 1030, and 240 tonnes (t) of N, P, K, Fe, Zn, Mn, and Cu, respectively, can be available and that helps in saving of costly chemical fertilizers. Conclusions Application of sugarcane industries by-products reduces the recommended dose of fertilizers and improves organic matter of soil during the crop production. It can also be used in combination with inorganic chemical fertilizers and can be packed and marketed along with commercial fertilizer for a particular cropping system. That helps in reduce the storage problem of sugarcane industries by-products across the India.